The Influence of Brand Image and Quality Perception on Acer Laptop Purchase Decisions at Sinar Karya Computer Manna, South Bengkulu Regency - Rizka Safitri; Ida Anggriani; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of brand image and perceived quality on purchasing decisions of Acer Laptops at Sinar Karya Computer Manna. The samples used in the study were consumers of acer laptops in Sinar Karya computers as many as 50 customers who came to the store. Data collection is done by using quantitative. The method used is multiple linear regression analysis using SPSS version 16.0 and hypothesis testing in these observations using t test and F test. Multiple Linear Regression Equation produces equation Y = 43.778+ 0.122 X1 +(-0.154 ) X2 . From these observations, Brand Image and perceived quality have a positive and significant effect on purchasing decisions. Based on the analysis of the coefficient of determination (R Square) of 0.36 which indicates that the variable Brand Image and perceived quality is able to contribute 36% of which 64% is influenced by other variables not examined in this study. The partial gain explains that the two independent variables are brand image and perceived quality with a value of t count < t table, namely 0.915 and 1.095 < t table 2.010. The two X variables have the greatest influence on the Y variable in Sinar Karya Computer Manna Kab. South Bengkulu.